The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.xpro.2021.100425
|View full text |Cite
|
Sign up to set email alerts
|

Cell population analysis of the adult murine subependymal neurogenic lineage by flow cytometry

Abstract: Summary This protocol provides a flow-cytometry-based procedure to classify and isolate all cells of the adult rodent subependymal zone (SEZ) neurogenic lineage, without the need for reporter mice, into different cell populations, including three neural stem cell (NSC) fractions with molecular signatures that are coherent with single-cell transcriptomics. Additionally, their cycling behavior can be assessed by means of 5-ethynyl-2′-deoxyuridine (EdU) incorporation. Our method allows the isolation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Consistent with this, SEZ homogenates showed a 40% increase in cell yield (Fig. 5c); however, when we scored specific cell populations by flow cytometry [38,39], we found that the increase in NSCs (CD24 −/low GLAST + CD9 high cells) was within the range of the generalized hyperplasia of the tissue, whereas NPCs (GLAST − CD24 −/low EGFR + cells) were significantly overrepresented with an increase of 70% in Cdkn1b mutant mice (Fig. 5c).…”
Section: Regulation Of Sox2 By P27 Is Required For Timely Cell Cycle ...supporting
confidence: 79%
See 4 more Smart Citations
“…Consistent with this, SEZ homogenates showed a 40% increase in cell yield (Fig. 5c); however, when we scored specific cell populations by flow cytometry [38,39], we found that the increase in NSCs (CD24 −/low GLAST + CD9 high cells) was within the range of the generalized hyperplasia of the tissue, whereas NPCs (GLAST − CD24 −/low EGFR + cells) were significantly overrepresented with an increase of 70% in Cdkn1b mutant mice (Fig. 5c).…”
Section: Regulation Of Sox2 By P27 Is Required For Timely Cell Cycle ...supporting
confidence: 79%
“…6 b–d). As with regard to the neuronal lineage, doublecortin (DCX) + early neuroblasts generated from NPCs can proliferate once or twice as they retain EGFR and are sensitive to mitogens before they exit cell cycle as late nondividing EGFR − neuroblasts that constitute, by far, the largest population in the SEZ neurogenic niche [ 2 , 38 ]. We found that DCX + neuroblasts in wild-type mice had very low or undetectable levels of SOX2 and ASCL1 [ 40 , 41 ] together with high levels of p27 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations